Anestesi Regional Blok Subaraknoid untuk Seksio Sesarea Kehamilan Triplet, Ketuban Pecah Dini di Daerah – Laporan Kasus: Laporan Kasus - Ruthy, Vilia (Cermin Dunia Kedokteran, 2026)
Introduction: Triplet pregnancy is a high-risk pregnancy for both mother and baby, the risk of complications increases with the number of fetuses and maternal age. Cesarean section is the recommended for triplet or more. Spinal anesthesia with hyperbaric bupivacaine and an opioid adjuvant is the most popular neuraxial anesthesia for cesarean section and has been used safely in twin, triplet, and quadruplet deliveries. Case: A woman, 34 years old, G5P4A0 gravida preterm triplet result of insemination, and premature rupture of membranes. Weight 70 kg, height 160 cm, Mallampati 2, blood pressure 135/84 mmHg, pulse rate 140 x/minute, temperature 38.80C, SpO2 100% with binasal cannula. The patient underwent cesarean section with subarachnoid block regional anesthesia using hyperbaric bupivacaine and opioid adjuvant. Discussion: This case demonstrates that preterm premature rupture of membranes is a high-risk condition requiring comprehensive management, including the administration of antibiotics and corticosteroids, as well as the selection of an anesthetic technique that is safe for both the mother and the fetus. The use of spinal anesthesia with a combination of bupivacaine, morphine, and fentanyl provides effective analgesia, although vigilance regarding hypotension and opioid side effects remains necessary. Conclusion: Overall, appropriate management resulted in stable maternal outcomes with good neonatal conditions, as evidenced by satisfactory APGAR scores, despite the low birth weight.